Raising the Bar on Corporate Governance : A Study of Eight Stock Exchange Indices - Grimminger, Andreas D. (World Bank and the International Financial Corporation, Washington, DC, 2013)
Stock exchanges around the world have launched Corporate Governance Indices (CGIs), sometimes as part of a broader Environment, Social, and Governance (ESG) initiative. The comprehensive analysis of these indices presented in this study is the first of its kind, and it reveals that CGIs have a positive impact, enhancing legal and regulatory frameworks by extending governance criteria to develop objective and measurable benchmarks. The study also shows that CGIs present companies with an opportunity to differentiate themselves in the market and, ultimately, offer companies an incentive to adopt better governance practices. Nevertheless, as the process for vetting and evaluation of companies for inclusion in the indices continues to evolve, access to underlying methodologies, disclosure of the ratings and self-assessments of individual companies, and of overall monitoring processes and procedures can still be enhanced. This study reviews the different approaches used by stock exchanges to build indices incorporating corporate governance. In the case of ESG indices, the focus is on the governance component of these indices. The study also draws lessons from the stock exchange's experiences and highlights success factors and shortcomings. In particular it addresses the following key questions: (i) what are the key drivers for stock exchanges to launch CGIs; (ii) what are the critical building blocks in the construction of a CGI; (iii) what are the risks faced by those investing in CGIs.